The Impact of the Labour Relations Act on Minority Trade Unions: A South African Perspective - Johan Kruger; Clarence Itumeleng Tshoose (Potchefstroom Electronic Law Journal, 2013)
The advent of the new political dispensation in 1994 heralded the coming of a new labour dispensation. Labour relations and labour policies changed significantly from that which prevailed under the previous government. The review of the labour legislation framework was at that stage a priority for the new government, with specific focus on the review of the collective bargaining dispensation.